Snap bean international trade: present status and future prospects - Peterson, W; Henry, Guy (International Center for Tropical Agriculture, 1990)
International trade in fresh and processed vegetables has expanded considerably over the last 20 years. The volume of fresh vegetables traded is about three times the volume of processed vegetables. More than half of total world trade originates in Europe, in particular the EEC, and two thirds of world trade is between industrialized countries. The European demand for fresh snap beans appears to be strong. Significant increases in imports have occurred in the EEC, especially France, during the last five years. Little data exists on the trade of canned or frozen snap beans between developing and developed countries. However, China is major exporter of canned beans. Several other countries, like Kenya and Turkey are also attempting to capture a share of this trade. Developing countries may enjoy a comparative and competitive advantage as snap bean exporters, based on relatively lower wages and geographic location. Snap bean production trends for importers and exporters are discussed to shed light on the prospects for growth in import demand and the potential of the snap bean trade for developing countries. It is expected that most of the demand growth will occur in the Middle East, Far East and in Europe. (AS)